A patent registration and trading system based on blockchain. (1st September 2022) - Hu, Jian; Zhu, Peng; Qi, Yong; Zhu, Qingyun; Li, Xiaotong
Highlights: Design a patent registration and trading method based on blockchain. The proposed method allows participants jointly maintain the information. Patent information management and user privacy security are guaranteed. The proposed method improves the availability and value of patents. Abstract: The traditional process of patent registration and trading is very complex, often hindered by challenges related to information security and patent traceability. As a popular emergent technology, blockchain has several useful characteristics such as tamper proof, distributed data management, timestamp, asymmetric encryption, and smart contract. Built upon these characteristics, this paper develops a patent registration and trading system for improved information security, immutability, transparency, and traceability. This system includes functions of patent registration and storage, patent trading, user privacy protection during patent registration and trading process, and overall data access control. To validate the applicability of the proposed system, this paper builds a blockchain environment to simulate a patent registration and trading process. We further conduct a security analysis and an efficiency analysis to compare the proposed patent registration and trading process with the traditional process. Through these comparisons we show that the proposed blockchain-aided patent registration and trading system is effective in resolving several key patent protection challenges. Theoretical and managerial implications are also discussed to highlight the significance of our proposed method.